Properly Accounting for Domestic Violence in Child Custody Cases: An Evidence-Based Analysis and Reform Proposal - Choplin, Jessica M. (2019)
Promoting the best interests of children and protecting their safety and well-being in the context of a divorce or parentage case where domestic violence has been alleged has become highly politicized and highly gendered. There are claims by fathers’ rights groups that mothers often falsely accuse fathers of domestic violence to alienate the fathers from their children and to improve their financial position. They also claim that children do better when fathers are equally involved in their children’s lives, but that judges favor mothers over fathers in custody cases. As a consequence, fathers’ rights groups have engaged in a nationwide effort to reform the custody laws to create a presumption of equal parenting time, with no exception when one of the parents has engaged in domestic violence. Domestic violence survivors and their advocates, however, claim that the needs of survivors of domestic violence and their children to be safe and free from further abuse are not being met in custody cases, that their claims of abuse are not being believed, and that the harm when a parent commits domestic violence against the other parent is not being recognized and addressed by judges and the family law professional upon whom they rely. This Article first presents a literature review, with articulated scientific standards applied to each of the pieces of research cited in this review, on what is happening outside of court and in court relating to domestic violence and best practices for taking domestic violence into account in these child custody cases. Among the key findings from this literature review are: (1) when a parent commits domestic violence against the other parent, this can cause serious long-term harm to children, (2) custody judgments tend to favor fathers over mothers because greater weight is placed on claims of alienation than on domestic violence claims, (3) long-term harms can be mitigated by evidence-based best practices, most notably, supporting non-abusive parents in their efforts to protect themselves and their children from further domestic violence, (4) family law judges and professionals must be trained on domestic violence and its nuances, as well as how to screen for domestic violence, to adequately support them, and (5) a component of this training is learning how to distinguish mutual “situational couple violence” for which “parallel parenting” custody arrangements might be feasible, from a pattern of “coercive abuse,” where sole decision-making and primary parenting time should be ordered to the non-abusive parent, and protective restrictions on parenting time should be ordered to the abusive parent. The Article then reports on a fifty-state review of custody-related laws (laws determining which parent makes major decisions relating to the child, who is allocated primary parenting time, and whether protective restrictions shall be placed on the parenting time of a parent who has engaged in domestic violence). This review found serious gaps between what evidence-based best practices suggest, and what is currently required by law in many states. These gaps in the law, including the failure of the law to require domestic violence screening and training for judges and other family law professionals, contribute to poor custody decision-making by them that compromises the safety and welfare of domestic violence survivors and their children. The Article then proposes nuanced law reforms that would align custody-related laws with evidence-based best practices for taking domestic violence into account in custody cases, including creating rebuttable presumptions, burdens of proof, and definitions of domestic violence that conform with these evidence-based best practices